Design, development and evaluation of The Manila City Library Software a library orientation and instruction program - Bartolome, Sharon G.; Panopio, Dennis P. (2002)
The Manila City Library Software was developed to aid users in their library search. It was developed to study its acceptability and usability. The program consists of four parts: a. profiles features the library's organizational goals, history, department functions, library service outlets, hours of operation, library activities and public library service; browse titles; c. maintenance; c. exit.